Distribution of Light Intensities of a Solar Bottle Bulb - Bo-ot, Luis Maria T.; Redulla, Cherry Dara S. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 6, 2019)
Solar bottle bulbs (SBB) have been proposed as an inexpensive, eco-friendly alternative to electric lighting in dense residential settlements typically found in urban areas. Interestingly, little testing has been done to verify a solar bottle bulb’s performance in terms of light quality. Sunlight with which the solar bulbs operate is dependent on local geographical and climatic conditions. This study aims to describe the amount of light output of a solar bottle bulb by plotting and investigating the distribution of light intensities transmitted indoors. This is done by measuring light levels at every one meter for every 15 degree angle from nadir, on two perpendicular planes to produce a polar graph. The polar graph indicates at which points light redistribution is at its highest intensity. Results from the data should provide insight into the effectiveness of the solar bottle bulb in terms of providing the minimum lighting requirements for a given space.